Recombinant human growth hormone promotes wound angiogenesis in burned mice through the ERK signaling pathway: Effect of rhGH on burn wound repair - Shao, Yang; Han, Mei; Chen, Guoyue; Song, Guodong (Cellular and Molecular Biology, 2024)
Burns are the most severe type of trauma, and the resulting ischemia and hypoxia damage can promote the dysfunction and even failure of tissues and organs throughout the body, endangering patients’ life safety. Recombinant human growth hormone (rhGH) has the functions of promoting protein synthesis to reverse negative nitrogen balance, accelerating wound healing, and improving immune function, which is widely used in the treatment of burns. However, the exact mechanism and pathway of rhGH’s action is not yet fully understood. In this study, we observed the wound repair effect of recombinant human growth hormone (rhGH) on burned mice and further analyzed the mechanism of action, which can provide more comprehensive reference opinions for clinical practice. First, by establishing a burn mouse model and and intervening with different doses of rhGH, we found that the wound healing capacity of mice was significantly enhanced and the inflammatory and oxidative stress responses were obviously alleviated, confirming the excellent promotion of wound repair and anti-inflammatory and antioxidant effects of rhGH. Subsequently, we found that the expression of p-ERK1/2/ERK1/2, EGF, TGF-β, and VEGF proteins was elevated in the traumatic tissues of mice after rhGH intervention, suggesting that the pathway of action of rhGH might be related to the activation of ERK pathway to promote the regeneration of traumatic capillaries.